2021
DOI: 10.1007/s42973-021-00092-w
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off between job losses and the spread of COVID-19 in Japan

Abstract: This paper quantitatively analyzes the trade-off between job losses and the spread of COVID-19 in Japan. We derive an empirical specification from the social planner’s resource constraint under the susceptible, infected, recovered, and deaths (SIRD) model and estimate how job losses and the case growth rate are related to people’s mobility using the Japanese prefecture-level panel data on confirmed cases, involuntary job losses, people’s mobility, and teleworkability. Our findings are summarized as follows. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Each indicator shows the percentage change in the number of visitors to (or time spent in) different locations compared to the baseline number computed from January 3rd and February 6th, 2020. Using four of these mobility measures -"Grocery and pharmacy', "Retail and recreation", "Transit stations", and "Workplace" -, we calculated the monthly average values of Google Mobility indicators, following the definition of [45,46].…”
Section: Possible Confoundersmentioning
confidence: 99%
“…Each indicator shows the percentage change in the number of visitors to (or time spent in) different locations compared to the baseline number computed from January 3rd and February 6th, 2020. Using four of these mobility measures -"Grocery and pharmacy', "Retail and recreation", "Transit stations", and "Workplace" -, we calculated the monthly average values of Google Mobility indicators, following the definition of [45,46].…”
Section: Possible Confoundersmentioning
confidence: 99%
“…Because WFH is an effective means of controlling the spread of infection and maintaining economic activity, many studies have found that its spread has mitigated its negative impact on GDP and employment (e.g., Eberly et al, 2021;Hoshi et al, 2021;Kawaguchi et al, 2022). Fujii and Nakata (2021) and Jones et al (2021) used the susceptible-infectious-recovered (SIR) macro model to analyze the effects of WFH on the trade-off between output and infection.…”
Section: Introductionmentioning
confidence: 99%